Adult attention deficit hyperactivity disorder in patients with fibromyalgia syndrome: Assessment and disabilities. (April 2021) - Pallanti, Stefano; Porta, Francesco; Salerno, Luana
Abstract: In the broader list of cognitive concerns, neuropsychological testing has shown that attentional impairment may have a specific burden in Fibromyalgia Syndrome (FMS). Preliminary observations have reported a subset of FMS patient screened for attention disorders fulfilling the actual diagnosis of ADHD, a neurodevelopmental disorder characterized by developmentally inadequate levels of inattention, hyperactivity and impulsivity that might persist in adulthood. Yet, no study to date has systematically examined the history and the specific contribution of ADHD to FMS in terms of clinical impact and related specific disabilities. In this study, 106 individuals with a FMS diagnosis based on the 2010 criteria of the American College of Rheumatology have been assessed for (a) the presence of ADHD; (b) the burden of disability caused by ADHD versus FMS; (c) the presence of other psychiatric disorders. Results indicated that ADHD was present in 24.5% of FMS individuals, it was associated with higher FMS symptoms severity and a greater functional impairment, particularly in the work/school domain. Moreover, patients with both FMS and ADHD had higher frequency of substance use disorders than those with FMS only (38.5% versus 3.8%) and mainly opioids. Overall, results suggest that ADHD can increase burden adding specific disability in work and social activities, and it is associated with a trend for the excessive use of opioid painkillers. Detection of neurodevelopmental and actual symptoms of ADHD is highly recommended especially in patient prone to increase the dose of anti-pain medication. Highlights: 24.5% of individuals with FMS also have ADHD. Impairment due to ADHD brings increased total functional and even specific disability. ADHD is associated with increased use of opiate and sedative drugs.